Strength properties of high-performance concretes with carbonate coarse aggregate - Góra, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
High performance concretes were tested to find an effect of the three different coarse aggregates (basalt, granite and dolomite) on concrete strength properties. All the results were analyzed statistically. Splitting tensile strength of high performance concrete with dolomite aggregate was significantly higher than that of concretes with basalt and granite aggregate. The effect of dolomite aggregate on compressive strength of HPC was much more advantageous than that of granite aggregate.